2016
DOI: 10.3390/atmos7020029
|View full text |Cite
|
Sign up to set email alerts
|

The Teleconnection of the Tropical Atlantic to Indo-Pacific Sea Surface Temperatures on Inter-Annual to Centennial Time Scales: A Review of Recent Findings

Abstract: Abstract:In this paper, the teleconnections from the tropical Atlantic to the Indo-Pacific region from inter-annual to centennial time scales will be reviewed. Identified teleconnections and hypotheses on mechanisms at work are reviewed and further explored in a century-long pacemaker coupled ocean-atmosphere simulation ensemble. There is a substantial impact of the tropical Atlantic on the Pacific region at inter-annual time scales. An Atlantic Niño (Niña) event leads to rising (sinking) motion in the Atlanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 60 publications
8
76
0
Order By: Relevance
“…Anomalous ascending motion and surface low pressure is also seen over the tropical North Atlantic from the simulated upper-level divergence and SLP fields, in agreement with a recent observational based analysis43, and this is due to the heating effect of the AMO warm SST anomaly. Consistent with simulation results found here, there has also been some observational evidence in the literature that an anomalous low (high) and ascending (descending) motions tend to occur over western Pacific when the Atlantic is warmer (colder) than normal, as manifested by the SLP field354344 and the zonal overturning circulation37. The anomalies of SLP and vertical motion are closely related to the change in cloud cover over the WTP, and thus can lead to the occurrence of the SST–SLP–cloud–longwave radiation positive feedback.…”
Section: Resultssupporting
confidence: 91%
“…Anomalous ascending motion and surface low pressure is also seen over the tropical North Atlantic from the simulated upper-level divergence and SLP fields, in agreement with a recent observational based analysis43, and this is due to the heating effect of the AMO warm SST anomaly. Consistent with simulation results found here, there has also been some observational evidence in the literature that an anomalous low (high) and ascending (descending) motions tend to occur over western Pacific when the Atlantic is warmer (colder) than normal, as manifested by the SLP field354344 and the zonal overturning circulation37. The anomalies of SLP and vertical motion are closely related to the change in cloud cover over the WTP, and thus can lead to the occurrence of the SST–SLP–cloud–longwave radiation positive feedback.…”
Section: Resultssupporting
confidence: 91%
“…In general, the SST anomaly patterns of the mean states show a combination of the PDO and AMO‐related anomaly patterns in the Pacific Ocean, and the strongest AMO‐related anomaly signals in the Atlantic Ocean with almost antisymmetric SST anomaly patterns in the northern and southern extratropical sectors of this Ocean (Figure ). Our analysis provided further indications on the previously discussed negative multidecadal relation of the SST anomalies in the Pacific and the Atlantic (Kucharski et al ., , ). One of them is the shortness of the mean states when the AMO and PDO are both in positive or negative phases in relation to those when they are in opposite phases.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Kucharski et al . () showed that the WAMO leads to a cooling in the eastern Pacific and a warming of the western Pacific and Indian Oceans, and the CAMO, to opposite conditions in these oceanic areas. McGregor et al .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much effort has gone into understanding the factors that cause variations in ENSO behavior. These include stochasticity or weather noise (e.g., Blanke et al, ; Eckert & Latif, ), chaos stemming from the deterministic nonlinear ocean‐atmosphere dynamical system and the annual cycle (e.g., Jin et al, ; Münnich et al, ; Neelin et al, ; Tziperman et al, ), as well as changes in the background climate state (e.g., Fedorov & Philander, ; Wang & An, ) and processes external to the tropical Pacific (e.g., Kajtar et al, ; Kucharski et al, ; Terray et al, ). Investigating these processes requires the use of climate models of a certain degree of complexity, such as a simple conceptual model (e.g., Jin, ; Suarez & Schopf, ), an intermediate complexity model (e.g., Zebiak & Cane, ), or a comprehensive general circulation model, depending on the extent to which particular processes need to be isolated and controlled.…”
Section: Enso In a Nutshell And Topical Issuesmentioning
confidence: 99%